Perbaikan Tata Letak Fasilitas dengan Mempertimbangkan Keseimbangan Lintasan (Studi Kasus) - Priscilla Gandasutisna; Tanti Octavia (Jurnal Titra, 2016)
PT. X is a job-order plastic packaging industry using line flow in their floor. Currently, the company faces the imbalance line flow and a long transportation time. The goal of this final project is to balance a production line and reduce the transportation time. A proposed facitily Layout and balanced production line are implemented. The result shows Line Efficiency for powder compact products increase from 61.83% to 80.77%, for pot products decrease 80.14% to 72.85% and for eyeshadow compact products increase 74.22% to 81.86%. A proposed layout gives the better solution compare to existing layout in term of moment.